MAKNA PESAN BENTUK DUKUNGAN DALAM FILM YANG BERJUDUL SLANK NGGAK ADA MATINYA - Denata, Aurora; Wisudawanto, Rahmat; Lukitasari, Evelyne Henny (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2016)
Film does not only as entertainment but also convey a message that can influence the people’s attitudes and perceptions. Film can also be used as a medium of anti-drug campaign. It conveys a message about the danger of drug abuse and describes a rehabilitation program for healing users. One film aims to anti-drug campaign is ‘Slank Nggak Ada Matinya’. This film is about the danger of drugs and the important role of the people who support and assist the member of Slank. The objective of this study is to find out the forms of social and family’s support and its meaning as described in the film ‘Slank Nggak Ada Matinya’. This study is qualitative descriptive. Data source for this study is the scenes in the film ‘Slank Nggak Ada Matinya, while the data are all the scenes in this film that contain elements of family and social support. This study used a two-stage analytical semiotic of Roland Barthes. The first stage is the analysis to determine the denotative meaning by seeing the scenes – that classified as data – and paying attention to the utterances of the actors that describe a form of support. The second stage is the analysisin determining the connotative meaning by seeing what the actors do in the scenes that shows family and social support The result of this study shows that the support appeared in the film ‘Slank Nggak Ada Matinya’ are social tangible support, social emotional support, social expectation support, family instrumental support and family informational support. Every scene contains various meaning, namely : (1) in the category social tangible support, the scene shows the direct aid and attention to his friends; (2) in social emotional support, it shows the close relationship between friends and family; (3) in social expectation support, it contains some advices indicated for friends; (4) in family instrumental support, it shows direct aids to the family member; (5) in family informational support, it shows a mother’s role in giving advice to her son